As inquirições medievais portuguesas (séculos XIII-XIV) : fonte para o estudo da nobreza e memória arqueológica : breves apontamentos - Pizarro, José Augusto de Sottomayor (2014)
The Portuguese Inquisitiones of the thirteenth and fourteenth centuries are among the richest sources of medieval Portuguese history, and are even unique in the European context. Initiated in 1220, in the beginning of the process of centralizing royal power, they were continued until the midfourteenth century, collecting a data set truly exceptional, not only by volume but by the wide range of approaches that their study permits. To study the Portuguese aristocracy they are one of the essential medieval sources, not only because they allowed analysis over a much extended chronological arch, but they also can be made through the same documental typology. But also to other issues, such as the evolution of the administrative/judicial map of the kingdom or wealth of ecclesiastical institutions, through anthroponomy, toponymy or Archaeology.